“Elaboración de vino a partir de uva variedad borgoña negra (vitis lebrusca). Usando azúcar invertido en tarapoto - San martín - Garcia Garay, Nelson (1998)
He present work is oriented to the development of came of grape variety Burgundy black (Vitis labrusca) using sugar inverted, whose cultivation is back to several decades in the area of Cumbaza, Region San Martin. Burgundy is a vigorous plant, clusters has conical form and medium size; beads are fo1ma ovoid, medium-sized and black violet; It must have high acidity, good aroma and color. The study was developed in two stages; a preliminary stage, where it rehearses the addition of inverted sugar in concentrations of 20, 25, 30 and 35 per cent, in grape musts which contains 14% soluble solids. The physicochemical characteristics were evaluated during the winemaking process, taking into account mainly the formation of alcohol and an analysis sensoriai by the emotional test (ivletodo 5-point hedonic scale); that determined the best treatment (30% soluble solids, with addition of invert sugar). The eta...